The Role of Islamic Religious Education Teachers in Establishing Religious Moderation in Generation Z - Ikrom Ikwanul Maula maula; Uswatun Khasanah; Ida Zahara Adibah (At Turots: Jurnal Pendidikan Islam, 2026)
This study aims to analyze the role of Islamic Religious Education teachers in establishing religious moderation in Generation Z in SMK Negeri 1 Pringapus of Semarang Regency. The background of the study is challenges faced by Generation Z as a digital generation that has wide access to information but is vulnerable to the influence of extreme ideologies, hoaxes, and opinion polarization on social media. This study used a descriptive qualitative method. The data were collected through observation and interviews with Islamic Religious Education teachers as main informants, and documentation as supporting data. Data analysis was carried out through data reduction, data presentation, and drawing a conclusion systematically. The results of the study showed that Islamic Religious Education teachers have a central role as role models, facilitators, and motivators in internalizing religious moderation values. The strategies used include open discussion, self-reflection, contextual case study, and providing motivation that is relevant to the characteristics of Generation Z. The main challenges are the influence of social media, peer environment, low digital literacy, and lack of dialogue within the family. Moreover, the supporting factors come from curriculum policies, support between teachers, and government policies related to strengthening religious moderation. This study concludes that the success of establishing religious moderation in Generation Z requires adaptive, collaborative, and role-based learning approaches, as well as synergy between school, family, and stakeholders to create generations that are tolerant, inclusive, and committed to national values.